Anthropometric characteristics of newborns with Prader–Willi syndrome. Issue 10 (30th July 2019) - Salvatoni, Alessandro; Moretti, Alex; Grugni, Graziano; Agosti, Massimo; Azzolini, Sara; Bonaita, Valentina; Cianci, Paola; Corica, Domenico; Crinò, Antonino; Delvecchio, Maurizio; Ferraris, Silvio; Greggio, Nella A.; et al.
Abstract: This is a retrospective multicenter nationwide Italian study collecting neonatal anthropometric data of Caucasian subjects with Prader–Willi syndrome (PWS) born from 1988 to 2018. The aim of the study is to provide percentile charts for weight and length of singletons with PWS born between 36 and 42 gestational weeks. We collected the birth weight and birth length of 252 male and 244 female singleton live born infants with both parents of Italian origin and PWS genetically confirmed. Percentile smoothed curves of birth weight and length for gestational age were built through Cole's lambda, mu, sigma method. The data were compared to normal Italian standards. Newborns with PWS showed a lower mean birth weight, by 1/2 kg, and a shorter mean birth length, by 1 cm, than healthy neonates. Females with a 15q11‐13 deletion were shorter than those with maternal uniparental maternal disomy of chromosome 15 ( p < .0001). The present growth curves may be useful as further traits in supporting a suspicion of PWS in a newborn. Because impaired prenatal growth increases risk of health problems later in life, having neonatal anthropometric standards could be helpful to evaluate possible correlations between the presence or absence of small gestational age and some clinical and metabolic aspects of PWS.